Factors Associated With Increased Estimated Blood Loss and Factors Associated With Utilization of Type and Screen in Benign Gynecology: A Retrospective Chart Review. Issue 2 (February 2023) - Jansen, Sierra M.; Ghatalia, Desna; Mayo, Alyssa; Lokke, Amanda; Petersen, Timothy R.; Serna-Gallegos, Tasha; Meriwether, Kate V.
Abstract : Importance: There is minimal literature discussing factors associated with increased estimated blood loss (EBL) or transfusion in gynecologic surgery in tertiary academic centers. Objective: The aim of the study was to determine factors associated with transfusion and increased blood loss during gynecologic surgery. Study Design: This retrospective cohort investigated patients undergoing benign gynecologic procedures at a tertiary medical center. We excluded women undergoing surgery for known or suspected malignancy, emergent surgery, obstetrical procedures, or cases with another surgical specialty. Patient age, body mass index, American Society of Anesthesiologists class, medical history, EBL, arterial line placement, preoperative laboratory studies, and transfusion receipt for up to 6 weeks postoperatively were extracted. The primary outcome was transfusion within 6 weeks of surgery; risk factors for high blood loss (EBL >500 mL) and transfusion were explored. Results: Nine hundred seventy-five surgical procedures were included (59% vaginal, 36% laparoscopic, 4% robotic). Median EBL was 50 mL (interquartile range, 10–100 mL). Estimated blood loss increased with duration of surgery ( P < 0.01). Transfusions were more likely to occur during open procedures (13%) compared with vaginal (2%), laparoscopic (2%), or robotic (3%). Arterial line placement (relative risk [RR], 11.8; 95% confidence interval [CI], 5.3–26.1) and additional intravenous placement (RR, 6.0; 95% CI, 2.6 to 13.7) were associated with transfusion. Vaginal surgery (RR, 0.13; 95% CI, 0.05 to 0.32) and urogynecologic procedures (RR, 0.1; CI, 0.01–0.7) were associated with reduced risk of needing transfusion. Conclusions: Most benign gynecologic surgical procedures have minimal blood loss. Patients undergoing surgery through minimally invasive routes or urogynecologic procedures are at further decreased risk of transfusion.